Relevant laboratory parameters in patients at hospital admission between July 2020 and October 2021 due to covid-19 at the Tesãi Foundation Hospital (Revista científica ciencias de la salud., 2022)
Background: in the fight against COVID-19, the identification of laboratory predictors in the progression of severe and fatal forms is urgently needed. Aims: to describe the alterations of laboratory parameters of patients diagnosed with COVID-19 at admission to Tesãi Foundation Hospital in Ciudad del Este-Paraguay between July 2020 to October 2021. Methods: A retrospective study using the medical charts of 103 patients admitted to the hospital due to a diagnosis of COVID-19 was carried out. Demographic, clinical, and laboratory data were collected at hospital admission. Results: 53.4% of the patients were male, mean age of 62.3±15.4 years, and 43.6% were admitted due to pneumonia. According to the complete blood count, 54.3% had lymphopenia, 26% thrombocytopenia, and 27% anemia. In the liver and kidney profiles, 37.9% had elevated urea levels, 56.3% elevated GOT levels, 26% elevated GPT, and 61% GGT levels. Regarding biomarkers, 80% had elevated LDH levels, 34% elevated D-dimer levels, 100% elevated C-reactive protein, 43.7% elevated procalcitonin, and 89.3% elevated ferritin. Significant differences (p